A numerical solution to nonlinear second order three-point boundary value problems in the reproducing kernel space - Lin, Yingzhen; Niu, Jing; Cui, Minggen (Applied mathematics and computation, 2012)
In this paper, a new numerical algorithm is provided to solve nonlinear three-point boundary value problems in a very favorable reproducing kernel space which satisfies all boundary conditions. Its reproducing kernel function is discussed in detail. We also prove that the approximate solution and its first and second order derivatives all converge uniformly. The numerical experiments show that the algorithm is quite accurate and efficient for solving nonlinear second order three-point boundary value problems.